Determinan Peningkatan Urbanisasi Di Negara-Negara ASEAN - Dafelia Qodhari; Khairul Umam Khudhori (Jurnal Magister Ekonomi Syariah, 2024)
The inevitable phenomenon of urbanization will have a bad impact if it is not balanced with wise policies that cause inequality in welfare between villages and cities, especially in developing countries. This study aims to measure and explain the relationship between the minimum wage, job opportunities, education, and economic growth to increase urbanization. The population in this study is from ASEAN countries, with a sample size of 8 countries: Indonesia, Malaysia, Thailand, Vietnam, Cambodia, Laos, Myanmar, and the Philippines. This study uses panel data processed with the Fixed Effect Model (FEM) approach. The study's findings show that any increase in minimum wage, employment opportunities, and economic growth will encourage an increase in urbanization, whereas education has no significant effect on the increase in urbanization in ASEAN countries. This needs to be done equally in the development of villages and cities by the government so that there is no gap in wages and job opportunities that can increase urbanization, causing problems of population density, increased crime, slums, and high carbon emissions in urban areas.